GIS-supported modelling of the accessibility of outpatient care services according to SGB V and SGB XI in Lower Franconia under consideration of demographic developments - Burk, Jannis; Meyer, Constantin; Peters, Jan Christoph; Rauch, Sebastian (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
The aim of this paper is to analyse the accessibility of outpatient care services in Lower Franconia, Germany, taking into account the spatially differentiated population structure for the year 2017 as well as the expected demographic development until 2025. The accessibility was modelled both raster-based and vector-based in a GIS software. Moreover, demographic developments in the age group “80 years and older” are also incorporated. The results of the raster-based travel time modelling show relatively good accessibility in the study area except from a few peripheral areas. Catchment areas for outpatient care services were calculated using vector-based travel time modelling, drawing on travel flat rates according to SGB V and SGB XI as well as staff costs as calculation bases for threshold values. In parts of Lower Franconia there is no sufficient cost coverage. With regard to the population development outlined above and insufficient coverage of travel costs by flat-rate travel allowances in low mountain ranges and away from urban agglomerations, a transition to a flexible travel compensation for nursing services and an increase in nursing staff is recommended.
Keywords: Accessibility analysis; GIS; Healthcare; Medical geography; Outpatient care; Lower Franconia